(untitled) (Revista Brasileira de Iniciação Científica, 2022)
The technology advance and the arrival of the pandemic caused by the Covid-19 virus has made online courses being focused among the various categories with Massive Open Online Course (MOOC), which has been used by several universities to enable educational means for their students by autonomous way, allowing them to access materials and videos from any device and at any time. The proposal of this work is to present an experience to build and provide a MOOC course about coteveryday informatics (e-mail and office toolbox) for students and teachers of basic education